THE INFLUENCE OF SALES TRAINING QUALITY, SALES EXPERIENCE, AND SMART WORKING ON SALESMAN PERFORMANCE - Wibawa, Hanasta Toar; Rahardja, Edy; Sukresna, I Made (Master of Management Diponegoro University, 2017)
The purpose of this research is to examine the influences of sales training quality, sales experience, and smart working on salesman performance. The research problem is how to increase salesman performance through sales training quality, sales experience and smart working?The sample of this research is the salesman from PT. Bank Pembangunan Daerah Jawa Tengah Semarang branch office, which amounted to 87 respondents. Data analysis using regression method that run with SPSS (Statistical Package Social Science) software. The results show that the sales training quality, sales experience and smart working effects on the salesman performance.The result of these research indicate that the influence of sales training quality significant on salesman performance; selling experience significant on salesman performance; and smart working significant on salesman performance.